Utilizing design intent information to aid in the synthesis of multi-domain systems. Issue 1 (2nd January 2017) - Bohm, Matt R.; Nagel, Robert L.; Riggs, Marie K.
ABSTRACT: The IDEAS (Iterative DEsign of Alternative Solutions) application is presented as a prototype engineering tool that enables design space exploration during the transition from problem clarification to concept generation based on initial form and fit design conceptualizations. The goals met through development of the application prototype are to demonstrate the feasibility of form and fit based design space exploration for engineered systems and to demonstrate the feasibility of abstracting functional design intent from a form and fit based engineering design paradigm. Meeting these goals is the first step toward developing a computational system that allows functional design intent to be captured and archived during conceptual design for use later in an existing suite of computational function-based design tools. GRAPHICAL ABSTRACT: